Peran Katekis-Awam dalam Mengemban Tri-tugas pada Lima Bidang Karya Gereka di Paroki Roh Kudus-Ru’a, Keuskupan Ruteng - Fransiska Widyawati; Leonardus Kanja (Kamaya: Jurnal Ilmu Agama, 2023)
The Catholic Church appoints lay catechists to carry out the duties of the faithful in the five areas of church duties. This article describes how lay catechists in the Parish of the Holy Spirit, Ru'a, in the Diocese of Ruteng in East Nusa Tenggara Province carry out the duties of the faithful in the five areas of church duties. The aim is to find models, forms, and challenges of lay catechist duties. The research method is descriptive qualitative, where five catechists serving in the Parish of the Holy Spirit Ru'a were interviewed in depth. In addition to them, the research also gathered information from the priest and parishioners where they work. As a result, the five lay catechists have played an essential role in five areas of the Church's pastoral work in Ru'a Parish. In carrying out their duties, they receive support and challenges from the people and the pastoral situation in the area. This research concludes that lay catechists in Ru'a Parish have carried out the tri-duties of the Church's mission according to the gospel mandate in the five areas of church duties. Their contribution has been positive in growing the faith of the people. However, they have faced many challenges, including the mindset of the people who valued the pastoral work of the clergy more than the laity. This study recommends that parishes pay more attention to the pastoral work of catechists and educate parishioners to have a more positive mindset in appreciating the pastoral work of lay catechists.